FDR and the Jews - Breitman, Richard 1947- (The Belknap Press of Harvard Univ. Press, 2013)
Introduction: Four Roosevelts -- The Rise and Fall of FDR -- FDR Returns -- The Democrat and the Dictator -- Immigration Wars -- Transitions -- Moving Millions? -- Resettlement in Latin America? -- Toward War -- Tightened Security -- Wartime America -- Debating Remedies -- Zionism and the Arab World -- The War Refugee Board -- Negotiations and Rescue in Hungary -- Endings -- Perspectives